Surface Reactions and Electronic Structure of Carboxylic Acid Porphyrins Adsorbed on TiO2(110) - Wechsler, Daniel; Vensaus, Priscila; Tsud, Nataliya; Steinrück, Hans-Peter; Lytken, Ole; Williams, Federico J. (Journal of Physical Chemistry C, 2021)
We studied the coverage- and temperature-dependent proton transfer and self-metalation reactions of tetraphenylporphyrin molecules containing a carboxyl functional group (MCTPP) on rutile TiO2(110) surfaces. Furthermore, we also determined changes in the molecular geometric and electronic structures as a function of coverage and temperature. The investigation was carried out by means of synchrotron radiation X-ray photoelectron spectroscopy and near-edge X-ray absorption fine structure measurements. We found that at a coverage of 0.2 ML, most MCTPP molecules adsorb with the iminic nitrogen atoms protonated; at 0.5 ML, a decrease in the proportion of protonated molecules is observed; and at a monolayer coverage, most molecules are not protonated. Raising the temperature to above 500 K, where hydroxyl groups recombine to desorb as water, causes a decrease in the number of protonated porphyrin molecules. In roughly the same temperature range, we start to observe the self-metalation of the free-base molecules, which produces flat-lying titanyl porphyrin molecules on the TiO2(110) surface. This reaction is found to be coverage dependent: For 0.2 ML, it starts above 450 K, and for 1.0 ML, temperatures above 650 K are needed. Metalation shifts the surface state located in the semiconductor band gap to lower energies. Our results suggest that protonation and self-metalation depend on the proximity of the macrocycle to the surface and show that metalation modifies the molecular occupied and vacant electronic states.
CRIS-Team WoS Importer:2021-05-07